1974
DOI: 10.1037/h0081981
|View full text |Cite
|
Sign up to set email alerts
|

Starting procedures and the vicious circle phenomenon.

Abstract: Following escape training, response persistence under punished-extinction conditions were evaluated using either a drop-start or gate-lift method of initiating each trial. The absolute level of response persistence was significantly greater when tested using the drop-start technique regardless of starting method used during training. It is suggested that the vicious circle phenomenon may be a consequence of this experimental procedure rather than the result of experimental subjects' behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
1980
1980

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Moreover, in those studies , the guillotine-door procedure did not produce self-punitive respondin g, but it did produce such respondin g in the present study . In add ition, in other research reported by Delude (1974) , alley-punished animals run with the drop-box procedure were found to be superior to those run with the guillotine-door procedure; no such differences were obtained in the present stud y. None of the above-cited studies employed a formal CS, however, such as a buzzer or tone , and other research (Babb, 1980) suggests that responding with the guillotine door may be facilitated by the addition of an efficient formal CS.…”
Section: Resultsmentioning
confidence: 83%
“…Moreover, in those studies , the guillotine-door procedure did not produce self-punitive respondin g, but it did produce such respondin g in the present study . In add ition, in other research reported by Delude (1974) , alley-punished animals run with the drop-box procedure were found to be superior to those run with the guillotine-door procedure; no such differences were obtained in the present stud y. None of the above-cited studies employed a formal CS, however, such as a buzzer or tone , and other research (Babb, 1980) suggests that responding with the guillotine door may be facilitated by the addition of an efficient formal CS.…”
Section: Resultsmentioning
confidence: 83%